2014
DOI: 10.4276/030802214x14044755581664
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Economic Evaluation in Occupational Therapy: Cost-Effectiveness of Pre-Discharge Home Visits after Stroke (HOVIS)

Abstract: Occupational therapy interventions, such as home visits, have been identified as being resource-intensive, but cost-effectiveness analyses are rarely, if ever, carried out. We sought to estimate the cost-effectiveness of occupational therapy home visits after stroke, as part of a feasibility study, and to demonstrate the value and methods of economic evaluation. Method: We completed a cost-effectiveness analysis of pre-discharge occupational therapy home visits after stroke compared with a hospital-based inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 21 publications
0
48
0
Order By: Relevance
“…The average cost of a home visit in this study was £208. A health economic analysis in this study (Sampson 2014) found that the mean total cost of a home visit was £183, compared with £75 for a hospital interview. Home visits were slightly more effective, resulting in a cost per quality-adjusted life year of just over £20,000.…”
Section: Published 2013 Drummondmentioning
confidence: 66%
“…The average cost of a home visit in this study was £208. A health economic analysis in this study (Sampson 2014) found that the mean total cost of a home visit was £183, compared with £75 for a hospital interview. Home visits were slightly more effective, resulting in a cost per quality-adjusted life year of just over £20,000.…”
Section: Published 2013 Drummondmentioning
confidence: 66%
“…This requires examination of pre‐discharge home visits’ effectiveness, evaluation of patient selection and development of criteria for pre‐discharge home visits (Atwal et al ., ; Lannin et al ., ; Lockwood et al ., ). Economic evaluation and demonstration of cost‐effectiveness is also essential (Sampson et al ., ; Wales et al ., ). On this background, the current study suggests work is needed to support best practice and ensure therapists of all skill levels can facilitate individual patient need being met.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges to pre‐discharge home visits include time and resource availability (Atwal et al ., ; Lannin et al ., ; Lockwood, Taylor, Boyd & Harding, ; Sampson, James, Whitehead & Drummond, ; Whitehead et al ., ), potential patient anxiety (Atwal et al ., , ) and potential for older adults to feel uninvolved in decision‐making particularly in relation to future caregiving (Atwal, Spiliotopoulou, Plastow, McIntyre & McKay, ). Occupational therapy practice is reported to be heavily influenced by organisational pressures (Atwal et al ., ; Drummond, Whitehead, Fellows, Edwards & Sprigg, ; Lockwood et al ., ), and the multidisciplinary team (Whitehead et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that DPHVs are costly and high-risk interventions (Rousseau et al, 2013). They are resource-intensive (Sampson et al, 2014) and often require two therapists to attend a visit. Drummond et al (2012) found that the average time spent on DPHV was 223 minutes, this included report writing and preparation time for the visit.…”
Section: Literature Reviewmentioning
confidence: 99%